Accelerated Weathering and Water Absorption Behavior of Kenaf Fiber Reinforced Acrylic Based Polyester Composites - Salim, Muhamad Saifuddin; Ariawan, Dody; Ahmad Rasyid, Mohd Fadli; Mat Taib, Razaina; Ahmad Thirmizir, Mohd Zharif; Mohd Ishak, Zainal Arifin (Frontiers in Materials, 2020)
Nonwoven kenaf (KF) mat reinforced acrylic-based polyester bio-resin composites that were prepared by an impregnation process followed by compression molding. They were exposed to the durability test of accelerated weathering and water absorption. Accelerated weathering test through UV irradiation caused modification in chemical, mechanical, surface appearance and color change of the composites. Two competing reactions occurred throughout the exposure period, i.e. post crosslinking and photo-oxidation process. FTIR analysis revealed that the former occurred at the early stage of exposure while the latter towards the end of the exposure, exhibited by an accentuated increase in carbonyl and vinyl index. The post-crosslinking process contributes to the improvement in flexural properties and thermal stability of the composites, whereas the oxidation process does not. SEM observation showed that the degradation by photo-oxidation resulted in the formation of voids and blisters on composite’s sample. Water uptake of all composites was found to follow Fickian behavior. Good recoveries (exceeding 79 %) of flexural properties were obtained upon re-drying. However, a significant reduction in flexural strength and modulus was obtained in the wet state condition. SEM observation revealed that full recovery was not possible because of the impairment of the -matrix interfacial region. Relatively higher flexural properties were exhibited by alkali-treated KF composites even after the durability test due to the improved strength and –matrix adhesion following the treatment.